IMPLEMENTASI CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) DALAM PEMBELAJARAN BAHASA ARAB PADA MATERI TARIKH ADAB DI PONDOK MODERN DARUSSALAM GONTOR - Subakir, Fairuz; Agus Yasin; Ahmad Ario Sofian; Siti Nikmatul Rochma; Nuraeni Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Content and Language Integrated Learning (CLIL) in Arabic language learning on Tarikh Adab material at Pondok Modern Darussalam Gontor. A qualitative case study design was employed. Data were collected through observation, interviews, and documentation, and analyzed using an interactive model. The findings reveal that CLIL effectively integrates language and content learning, enhances students’ Arabic proficiency, and strengthens their understanding of Islamic historical knowledge. The approach also promotes active engagement and critical thinking skills. However, challenges include students’ varied language proficiency and teachers’ pedagogical limitations. This study contributes to the development of an integrative CLIL-based learning model within Islamic boarding school contexts.